Internal and Flanking Sequence from AFLP Fragments Using Ligation-Mediated Suppression PCR. (May 1999) - Schupp, James M.; Price, Lance B.; Klevytska, Alexandra; Keim, Paul
Amplification fragment-length polymorphism (AFLP) analysis has proven to be a powerful tool for developing a large number of reliable genetic markers across a wide variety of organisms. Often it is desirable to further characterize these markers by obtaining internal and flanking sequence information. Here, we present a systematic approach for obtaining such information from AFLP markers. AFLP fragments can be isolated from dried polyacryamide sequencing gels (that have been stored for extended periods of time), amplified using PCR and subjected to sequence analysis. Outwardly oriented locus-specific primers are designed from the internal sequence and used in conjunction with adapter primers to amplify unknown regions that flank the internal sequence from up to 22 different restriction-ligation (R-L) reactions. This often results in multiple reactions yielding products of appropriate size and specificity for direct sequencing without the need for a nested PCR, extensive gel purification or subcloning. The detailed protocol is presented with PCR results from a variable AFLP fragment from Bacillus anthracis .